2018
DOI: 10.5430/jnep.v8n7p60
|View full text |Cite
|
Sign up to set email alerts
|

Developing a measure for health professionals’ attitudes toward veterans

Abstract: U.S. veterans have complex healthcare needs that require professionals who are properly trained to address these issues. However, little is known about the attitudes that nurses and other professionals have toward veteran patients, particularly those working in community-based settings where it is unlikely training on veterans' issues has occurred. Understanding health professionals' attitudes toward caring for veterans is an important step in developing a workforce that is knowledgeable and willing to serve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“… Smothers et al (2018) conducted a systematic review of the literature of substance use education in schools of nursing and identified that the American Association of Colleges of Nursing, American Society for Pain Management Nursing, and American Nurses Association supported the increase for substance use education for nurses that includes outcome assessments. Knopf-Amelung et al (2018) conducted a study comparing three instructional methods to teach baccalaureate nursing students in the care of patients with SUD. The three instructional methods included (a) narrated slides, (b) an online course, and (c) an in-person role-play with classmates and standardized patient simulations.…”
Section: Nursing Education: Integration Of Suds Into Curriculummentioning
confidence: 99%
“… Smothers et al (2018) conducted a systematic review of the literature of substance use education in schools of nursing and identified that the American Association of Colleges of Nursing, American Society for Pain Management Nursing, and American Nurses Association supported the increase for substance use education for nurses that includes outcome assessments. Knopf-Amelung et al (2018) conducted a study comparing three instructional methods to teach baccalaureate nursing students in the care of patients with SUD. The three instructional methods included (a) narrated slides, (b) an online course, and (c) an in-person role-play with classmates and standardized patient simulations.…”
Section: Nursing Education: Integration Of Suds Into Curriculummentioning
confidence: 99%